Rules for detecting a radiometric signal in multi-channel reception - Кудряшов, В.Є.; Макуха, Б.А.; Самоквіт, В.І.; Ялоза, І.А. (Radiotekhnika, 2020)
Radiometric signal detection rules have been developed based on the likelihood of ratio method, provided that these radiometric signals are of Wiener-distributed non-stationary random process. Detection rules have been derived in the paper for a non-stationary signal against non-stationary interferences, including intrinsic noise of radiometric channels. Detection rules for two receiving positions (single-baseline system) and joint signal processing on four receiving positions (dual-baseline system) have been obtained. Physically existing minor simplifications have been injected. The feasible detection block diagrams have been created, accounting for the threshold levels, and according to radiometric signal detection rules in both single- and dual-baseline mapping systems. For unambiguous detection of useful signals, it is necessary to have scanning antenna systems. The width of the radiation patterns of the reception points antennas is determined by the area of the mapping spot. In this area there should be, for example, four intersections of the stroke difference. Implementation of a simplified scheme is possible on the basis of high-speed devices to ensure a sufficient signal compression ratio and the longest range of the system as a whole. At the output of the correlation detectors of each base, inter-base correlators are installed. At their outputs are threshold devices with a threshold level that is equal to the variance at the outputs between the base correlators, in the absence of useful signals. The use of a simplified scheme is possible not only in the millimeter (mm), or (and) in the infrared (IR) wavelength range. The use of the IR range significantly increases the resolving power with respect to the stroke difference. The implementation of the synthesized aperture mode of antennas in mm and IR wavelength ranges will allow high-quality mapping from the ground orbit of space objects.